Eksistensi Baitul Mal di Kota Langsa dalam Meningkatkan Kesejahteraan Masyarakat Miskin - Rizky Saputra (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2019)
Langsa city is one place of region in Indonesian who had applied shari’a islam, the accumulation institution of zakat named Baitul Mal. However the existence of this Baitul Mal evidently is not directly proportional with the enthusiasm peoples of Langsa city in paying zakat, infak, sedekah through Baitul Mal. The purpose of this research is to identifi cation optimization the fund distribu tion from Baitul Mal in Langsa city, and identifi cation the existence of Baitul Mal into increased the prosperous of poor peoples in Langsa city. This research is qualitative empirical research with using phenenomenology approach. From research result found the distribution fund from Baitul Mal in Langsa city has not eff ective yet to reduce the destitution. Baitul Mal has problems in dissimilation, transparency, and debts from muzakki. Baitul Mal has not able to increasement welfare of poor peoples. Zakat which is given has not get the target exactly and has not reach the goal to inereasement the poor peoples live.